Curriculum Reform In Indonesia: From Competency-Based To Freedom Of Learning - Simarmata, Herry Augustinus; Mayuni, Ilza (Pustaka Galeri Mandiri, 2023)
During the Covid-19 pandemic, an already existing learning crisis impacted Indonesian education lag, resulting in learning loss and widening learning gaps between regions and socioeconomic groups. Furthermore, as learning styles have shifted from traditional to technology-based learning methodologies, the current digitalization era is one of the benchmarks for the emergence of curriculum reform in Indonesia. Freedom of Learning Curriculum, also known as Kurikulum Merdeka, is a solution to today's problems in Indonesian education. This research is a qualitative study in which data is collected through documentation and literature techniques. The documents studied were books, notes, and previous research reports that focused on curriculum reform and curriculum freedom. The collected data was subsequently evaluated utilizing qualitative descriptive analysis techniques. The Kurikulum Merdeka was developed as part of the learning recovery effort as a more flexible curricular framework, concentrating on key materials and the development of student character and competences.